3D Research Challenges in Cultural Heritage V: Paradata, Metadata and Data in Digitisation - (:unkn) unknown (My University, 2024)
This open access book presents a collection of papers focussing on 3D digitisation in the domain of cultural heritage. The use of data acquisition technologies in digitising cultural heritage holds great potential for preserving and disseminating the history of mankind. However, to exploit these opportunities in full, comprehensive guidelines for documenting the process of digitisation are required. Only then can the efficiency and credibility of digital representations be assured. A major focus of the 16 papers included in this State-of-the-Art Survey is on all aspects of the documentation of the digitisation process, i.e., the paradata, which, alongside the metadata, is critical to the scientific rigour, replicability and sustainability of digital heritage resources. The volume provides a useful resource for computer scientists, surveyors, archaeologists, architects, museologists and engineers.
Keywords: Digital Heritage; Metadata; Paradata; 3D Data; 3D Digitization; Digital Documentation; Photogrammetry; Extended Reality; Digital Cultural Heritage; Digital Twin